Old World Bluestem Seedling Emergence and Vegetative Cover Following Glyphosate Treatment - K. R. Harmoney (Kansas Agricultural Experiment Station Research Reports, 2016)
Old world bluestems (OWB) are perennial warm-season grasses introduced into the U.S. from parts of Asia, eastern Europe, Africa, and Australia. The two most common old world bluestem species found in Kansas are yellow bluestem (Bothriochloa ischaemum), otherwise known as King Ranch bluestem, and Caucasian bluestem (Bothriochloa bladhii). These grasses were introduced for soil conservation and forage production in arid regions of the southern Great Plains; however, in Kansas and elsewhere, they have escaped areas where planted and have been invading native rangelands and pastures that were old crop fields seeded back to native grasses. Efforts to control OWB in native rangelands and native seeded pasture have had short term success, but the abundant seed produced from mature OWB plants has resulted in a soil seedbank capable of producing high populations of new seedlings. However, the length of time that this seedbank is capable of producing new seedlings has received relatively little investigation. The goal of this project was to evaluate new OWB seedling emergence from the soil seedbank for two years following OWB control with glyphosate.
Keywords: weed science